Effects of Upper-Body Resistance Exercises and Anxiety Levels on Free-Throw Performance in Basketball Players - Lukman Nul Hakim; Gigih Siantoro; Surono; Nurkholis; Fransisca J M Wijaya; Dewangga Yudhistira (STKIP Pasundan, 2026)
This study examined the effects of Medicine Ball Throw One Hand and Overhead Tricep Extension Resistance Band training on free throw performance, anxiety level, and their interaction among male high school basketball players. A 2×2 factorial design was employed involving 24 male athletes from SMAK Gloria 1 Surabaya. Anxiety was measured using the Competitive State Anxiety Inventory-2 (CSAI-2), with group assignment via Matched-Subject Ordinal Pairing (MSOP). Two-Way ANOVA was applied at α = 0.05. Results showed: (1) both training methods significantly improved free throw performance, with Overhead Tricep Extension Resistance Band being more effective (F = 18.615; p = 0.000); (2) anxiety level did not significantly affect free throw performance (F = 1.385; p = 0.253); (3) no significant interaction existed between training method and anxiety level (F = 0.000; p = 1.000). Overhead Tricep Extension Resistance Band training is recommended for improving free throw ability regardless of anxiety level.